Beurteilung von Belastung und Beanspruchung der unteren Extremitäten beim Training in einer Funktionsstemme - Hahn, A. D.; Tusker, F. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
A three-dimensional analysis of kinematics and dynamometric load parameters has been carried out when extending the lower limb at different velocities in a leg press. Once the external loads are known internal loads in the lower extremity can be calculated with simplified joint structures. In our case computing intersegment moments by applying the methods of inverse dynamics is proper for estimating the internal loads. It was found that there exists to a great extent a three-dimensional character of internal loads at all joints of the lower extremity. Therefore it is not possible to conclude a two-dimensional character of internal loads from an almost planar and simple movement. Thus only a two-dimensional analysis may underestimate internal loads up to 40 % in the ankle joints, 25 % in the knee joints, and up to 65 % in the hip joints. The comparison of ground reaction forces and the intersegment moments acting in the sagittal plane showed differences between the position of their maxima and the characteristic run of curves. Compared to previous two-dimensional approaches this analysis indicated that important parameters and the whole extent of internal loads can only be found in a complete three-dimensional analysis of movement.